Material driven machining process modeling. (October 2017) - Pan, Zhipeng; Liang, Steven Y.
Abstract: A material driven machining process modeling framework is proposed to incorporate thermal-mechanical-microstructural coupling in which the material microstructure dynamics and process mechanics are computed simultaneously. The material microstructure evolution in the machining process is obtained from dynamic recrystallization model which takes the strain, strain rate and temperature history as input. A microstructure sensitive flow stress model is used to correlate the material microstructure with material mechanical properties. The detailed implementation of the proposed framework is illustrated by the machining of titanium alloy. As the output of the model, the machining forces, residual stress profile and machined surface microstructure states are validated against the experiments.